2002
DOI: 10.1038/sj.mp.4001199
|View full text |Cite
|
Sign up to set email alerts
|

Decreased muscarinic1 receptors in the dorsolateral prefrontal cortex of subjects with schizophrenia

Abstract: To test the hypothesis that muscarinic receptors are involved in the pathology of schizophrenia, we measured muscarinic 1 (M1R) and muscarinic 4 (M4R) protein and mRNA as well as [ 3 H]pirenzepine binding in Brodmann's areas (BA) 9 and 40 obtained postmortem from 20 schizophrenic and 20 age/sex-matched control subjects. There was a significant decrease in [ 3 H]pirenzepine binding to BA 9 (mean ± SEM: 151 ± 15 vs 195 ± 10 fmol mg −1 ETE; P Ͻ 0.02), but not BA 40 (143 ± 13 vs 166 ± 11 fmol mg −1 ETE), from subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
148
5
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 191 publications
(165 citation statements)
references
References 27 publications
10
148
5
1
Order By: Relevance
“…84 More recent studies, using more selective radioligands such as [ 3 H]pirenzepine, suggested that levels of muscarinic M 1 and M 4 receptors are decreased in the caudate and putamen from subjects with schizophrenia 85,86 (see Table 1). Similar findings of decreased levels of muscarinic M 1 and M 4 receptors in schizophrenia have been reported in the hippocampus 87 and the prefrontal cortex, 88,89 but not in the parietal cortex. 89 Using the same cohort of subjects, no changes were seen in the levels of muscarinic M 2 and M 3 receptor protein and muscarinic M 2 and M 3 mRNA in the prefrontal cortex.…”
Section: Post-mortem Cns Studiessupporting
confidence: 85%
“…84 More recent studies, using more selective radioligands such as [ 3 H]pirenzepine, suggested that levels of muscarinic M 1 and M 4 receptors are decreased in the caudate and putamen from subjects with schizophrenia 85,86 (see Table 1). Similar findings of decreased levels of muscarinic M 1 and M 4 receptors in schizophrenia have been reported in the hippocampus 87 and the prefrontal cortex, 88,89 but not in the parietal cortex. 89 Using the same cohort of subjects, no changes were seen in the levels of muscarinic M 2 and M 3 receptor protein and muscarinic M 2 and M 3 mRNA in the prefrontal cortex.…”
Section: Post-mortem Cns Studiessupporting
confidence: 85%
“…[45][46][47] In addition, PLC-b1 KO mice have been shown to have aberrant changes in the cortex and hippocampus during development and in the adult 3,9,[27][28][29]48 to which [ 3 H]pirenzepine binding deficits may now be added. While the binding of [ 3 H]pirenzepine is not specific to a single muscarinic receptor, the relative densities of muscarinic receptors in the cortex and hippocampus and the relative affinity of muscarinic receptors for [ 3 H]pirenzepine 37 would suggest that PLC-b1 KO mice have decreased muscarinic M1 receptors in the cortex and muscarinic M1/M4 receptors in the hippocampus. Significantly, our data suggest that enrichment rescues these receptor levels in PLC-b1 KO mice without impacting upon receptor density in wild types.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this study we present our characterization of the phenotype of the PLC-b1 KO mice, including behavioral paradigms assessing endophenotypes representative of aspects of schizophrenia symptomatology, 30,31 under different environmental and pharmacological conditions. In addition, we have examined whether key markers in the dopaminergic, serotonergic and cholinergic pathways, which have been shown to be altered in the cortex of subjects with schizophrenia, 17,[32][33][34][35][36][37][38] are altered by the PLC-b1 mutation or environmental stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Of significance to findings on cortical [ 3 H]pirenzepine binding are recent data showing that a decrease in binding of that radioligand in BA 9 from subjects with schizophrenia was associated with a decrease in M1, but not M4, receptor protein and mRNA (Dean et al, 2002). It is therefore intriguing to postulate that decreased [ 3 H]pirenzepine binding in the cortex from subjects with schizophrenia is reflective of widespread decreases in levels of M1 receptors.…”
Section: Sirmentioning
confidence: 99%
“…In the case of the M1 receptor, it is significant that one of the prominent features of M1 receptor knockout mice is that they show abnormalities in cognitive-related behavior (Anagnostaras et al, 2003). This suggests that the M1 receptor has a significant role in maintaining normal cognitive function; this is especially significant given that subjects with schizophrenia have cognitive deficits (Pantelis et al, 1999) and low levels of cortical M1 receptors (Dean et al, 2002). The hypothesis that deficits in cortical M1 receptors may be related to cognitive deficits in schizophrenia has been further advanced by a recent study that showed that a C267C genotype at a A276C single-nucleotide polymorphism in the M1 receptor gene was associated with poor cognitive function in subjects with schizophrenia (Liao et al, 2003).…”
mentioning
confidence: 99%